Some observations on wild geese in Spitsbergen - Blurton Jones, N G; Gillmor, Robert (Wildfowl, 1959)
The authors spent two weeks at a nesting colony of Pink-footed Geese at De Geerdalen in Icefjord. Eighteen nests were found containing an estimated 67 eggs and producing about 30 goslings, mostly hatching unusually early, from 27 June onwards, the peak hatching date being 29 June. Females brooded eggs and goslings in the nest for very long spells. They varied in their readiness to leave the nest when disturbed. Males stayed on guard near the nest, sometimes going away to drink and bathe. They also spent must time on the alert when the family had left the nest. Goslings spent approximately one day in the nest, eventually making excursions from under the female to feed and then being led away by the female. One female deserted her goslings which were adopted by another pair. In the wild Pinkfoot goslings follow their parents poorly at first but soon improve. At first families were single and scattered, some form flocks of families and eventually they join broodless adults. Goslings can fly only a short time before the probable date of departure. Observations on relations between geese and foxes are conflicting. Pinkfeet seem to have survived disturbance in Icefjord better than Brents and Barnacles. Forty Barnacles, including 9 goslings, were watched in Sassendalen. Twenty-eight Brent Geese, including 7 goslings, were seen in Austfjord. Surprisingly few Pinkfeet were seen in Sassendalen.